Site formation processes at Manot Cave, Israel: Interplay between strata accumulation in the occupation area and the talus. Issue 160 (November 2021) - Berna, Francesco; Boaretto, Elisabetta; Wiebe, Matthea C.; Goder-Goldberger, Mae; Abulafia, Talia; Lavi, Ron; Barzilai, Omry; Marder, Ofer; Weiner, Stephen
Abstract: Manot Cave contains important human fossils and archaeological assemblages related to the origin and dispersal of anatomically modern humans and the Upper Paleolithic period. This record is divided between an elevated in situ occupation area and a connecting talus. We, thus, investigated the interplay between the accumulation of the sediments and their associated artifacts in the occupation areas and the translocation of part of these sediments and artifacts down the talus. We examined the lithostratigraphy of two excavation locations in the occupation area (areas E and I), and two in the talus (areas C and D). We also assessed the diagenetic processes that have affected all these areas. A linear array of stalagmites and stalactites separates the occupation area from the talus, demarcating a major topographic barrier between the two. We infer that during human occupation, sediment accumulation of soil, wood ash, and bone was rapid and that some sediments with their associated artifacts overflowed the barrier and translocated down the talus. During periods of nonoccupation, the ash in the occupation area partially dissolved owing to the release of acid from the degrading bat and bird guano, and the layer thicknesses decreased. The south side of the talus (area C) has a normally stratified archaeological record, with the older archaeological materials underlying the younger materials. This suggests that the barrier between the occupation area and area C was relatively shallow and allowed a fairly continuous sediment accumulation in the talus. In the central part of the talus (area D), the stratigraphy is complex and shows mixing, presumably owing to the steep underlying bedrock topography and the mixing that occurs when sediments move down a steep slope. Finally, the distribution of secondary phosphates is consistent with the location of a main cave entrance to the south of the Paleolithic occupation area.